Multi-frequency amplitude-programmable metasurface for multi-channel electromagnetic controls - Wu Rui Yuan; He Shi; Wu Jun Wei; Bao Lei; Cui Tie Jun (Nanophotonics)
The digital and programmable metasurfaces, as opposed to conventional metasurfaces, offer a more sophisticated method of collaborating information and physics, showcasing several real-time controls to electromagnetic (EM) ways in succinct ways. In this work, we propose a multi-frequency amplitude-programmable (MFAP) metasurface with multiple frequency channels to enhance the presentation and manipulation of EM data. With this metasurface, the reflected amplitudes can be simultaneously and independently encoded between high (digit “1”) and low (digit “0”) levels. The amplitude code is unique, which exhibits both reflection coefficients and radiation patterns to allow for flexible multi-functional EM operations with frequency. For instance, the MFAP metasurface can be used to design innovative communication systems by transmitting various EM signals individually across the channels in time domain. It is also possible to carry out multi-bit transmissions by mixing these frequency channels. By introducing complex coding patterns in space domain, it is possible to manipulate EM powers with greater precision. A square-split ring meta-atom that can achieve stable single-frequency amplitude control and multi-frequency 1 bit amplitude-programmable features is described as a proof-of-concept. Varactors loaded on metallic structures of various sizes are switched between operating states to modify the amplitude codes at each frequency channel. The suggested MFAP metasurface’s validity is confirmed by simulations and measurements from a dual-channel MFAP metasurface prototype.